2021
DOI: 10.1111/fwb.13711
|View full text |Cite
|
Sign up to set email alerts
|

When and where are catfish fat fish? Hydro‐ecological determinants of energy reserves in the fork‐tailed catfish, Neoarius graeffei, in an intermittent tropical river

Abstract: The cultural and ecological importance of fork‐tailed catfish, Neoarius graeffei, in northern Australia is linked to its energy stores, or how fat fish are. Water resource development that alters river flow has the potential to impact the energy stores of fork‐tailed catfish. We investigated the influence of flow and habitat on the energy reserves of fork‐tailed catfish during the dry season in an intermittent wet–dry tropical river using data collected in three years with different flow volumes from a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
(122 reference statements)
1
3
0
Order By: Relevance
“…The high productivity booms from large floods are likely to increase food availability and quality, allowing for higher growth rates of fish during the wet season as well as the early dry season. Similar trends have been observed in previous studies which have found larger individuals or better body condition of individuals following larger floods in dryland rivers (Balcombe et al, 2012; Beesley et al, 2021; Lear et al, 2021). It is interesting that the opposite pattern was distinctly observed in C. lentiginosus ; it is possible that this dry season specialist does not forage well under conditions typically observed in years with larger wet seasons, including higher flow rates and deeper pools, and therefore has reduced growth rates or reduced survival of large individuals during wetter years.…”
Section: Discussionsupporting
confidence: 90%
“…The high productivity booms from large floods are likely to increase food availability and quality, allowing for higher growth rates of fish during the wet season as well as the early dry season. Similar trends have been observed in previous studies which have found larger individuals or better body condition of individuals following larger floods in dryland rivers (Balcombe et al, 2012; Beesley et al, 2021; Lear et al, 2021). It is interesting that the opposite pattern was distinctly observed in C. lentiginosus ; it is possible that this dry season specialist does not forage well under conditions typically observed in years with larger wet seasons, including higher flow rates and deeper pools, and therefore has reduced growth rates or reduced survival of large individuals during wetter years.…”
Section: Discussionsupporting
confidence: 90%
“…Mouthbrooding in fishes is likely to be a particularly costly parental care investment for the caring parent, where the ability of brooders to ingest food and conduct normal gill function is likely to be af- (Jakob et al, 1996;Le Cren, 1951) can be influenced by season, reproductive state (spawning), morphological factors and the availability of resources in the environment (Abecia et al, 2018;Beesley et al, 2021;Luiz et al, 2019). In our study, brooders of both species showed a general reduction in at least one body condition index relative to nonbrooders.…”
Section: Discussionmentioning
confidence: 50%
“…The diversion of body energy resources from tissue maintenance to caring for young is an important potential reproductive cost to the adult care giver (Alonso‐Velando & Alvarez, 2012). Variations in relative body condition (often used a proxy measure of body fitness in fishes (Jakob et al, 1996; Le Cren, 1951) can be influenced by season, reproductive state (spawning), morphological factors and the availability of resources in the environment (Abecia et al, 2018; Beesley et al, 2021; Luiz et al, 2019). In our study, brooders of both species showed a general reduction in at least one body condition index relative to nonbrooders.…”
Section: Discussionmentioning
confidence: 99%
“…This project used scientific knowledge from the ecological and hydrological disciplines to determine the water requirements for the significant aquatic fauna and riparian plants (e.g., Beesley et al, 2020;Burrows et al, 2020;Beesley et al, 2021;Canham et al, 2021). Two main groups of non-academic actors were involved in the project: government scientists and planners, and Traditional Owners and Indigenous rangers.…”
Section: Fish and Riparian Vegetation Water Requirementsmentioning
confidence: 99%